Media Ownership and Monopoly: Legal Oversight and Public Interest Concerns in Pakistan - Dr. Hafiz Abdul Rehman Saleem; Nazia Bano; Jawad khalil Pitafi, (Dialogue Social Science Review (DSSR), 2025)
The pluralism of the media provides an indispensable element of democratic society, making sure that a variety of views, voices and stories is reflected in the arena of the public opinion. Nevertheless, there is a high rate of media ownership concentration in the hands of highly influential and wealthy media conglomerates in Pakistan and this has triggered serious doubts on accountability concerning democracies, freedom of expression and protection of the interest of people. The present paper is an attempt to examine the legal checks and balances, or rather the absence of the same, regarding the ownership of media in Pakistan with particular emphasis on the ramifications of the monopoly in information publishing. The paper proposes that the media concentration in ownership will compromise the democratic values that are embedded in the Constitution of Pakistan, especially the liberty of speech and access of various source of information defined under Article 19. Despite having the supposed existence of bodies like Pakistan Electronic Media Regulatory Authority (PEMRA) and Competition Commission of Pakistan (CCP) which are meant to curb the competition in media and limit the exercise of monopoly, their ability to enforce their findings is doubtful. The regulatory system governing media ownership in Pakistan is diversified, out-mode and in most aspects, unsuitable to deal with the challenges of cross-media convergence and media companies’ consolidation. The biggest media houses including Jang/Geo, ARY, and Express have taken over the electronic media and have also been involved in the print and digital media to a great extent, constructing vertically and horizontally integrated media empires that control the opinion and political discourse of masses to a great extent. The paper also provides a wider picture to the situation of Pakistan through a comparative perspective with the regulatory practices of other jurisdiction like India, the United Kingdom, and European Union. Such comparative perspectives indicate how in other democracies balancing freedom of press against anti-monopolizing protection has been tried out so as to maintain a vibrant, competitive media. Conversely, regulatory framework in Pakistan is not only institutionally weak but also politically influenced, especially in cases of PEMRA that has had a continuous allegation of regulatory capture and lack of independence. To address the implication of the concentrated media ownership on the public interest, this paper will argue that the current system allows handpicking of reports, suppression of critics and backtracking of investigative journalism. The fact that transparency in media funding and ownership arrangement is done away with only adds to the malaise which leaves citizens at the mercy of biased and manipulated data flows. Conclusively, the paper requests that an ambitious agenda of legal change be put in place by introducing clear anti-concentration thresholds, strengthen institutional independence of media regulators, and the disclosure of ownership information. With such reforms only, can Pakistan harbor the prospects of preserving the democratic necessity of media pluralism and upholding the interest of the populace in the era of the monopolistic domination of information.